Highly bright near-infrared chemiluminescent probes for cancer imaging and laparotomy - Wei, Xin (2023)
Near-infrared (NIR) chemiluminescence imaging holds potential for sensitive imaging of cancer due to its low background; however, few NIR chemiluminophores are available, which share the drawback of low chemiluminescence quantum yields (ΦCL ). Herein, we report the synthesis of NIR chemiluminophores for cancer imaging and laparotomy. Molecular engineering of the electron-withdrawing group at the para-position of the phenol-dioxetane leads to a highly bright NIR chemiluminophore (DPT), showing the ΦCL (4.6×10-2  Einstein mol-1 ) that is 3 to 5-fold higher than existing NIR chemiluminophores. By caging the phenol group of DPT with a cathepsin B (CatB) responsive moiety, an activatable chemiluminescence probe (DPTCB ) is developed for real-time turn-on detection of deeply buried tumor tissues in living mice. Due to its high brightness, DPTCB permits accurate chemiluminescence-guided laparotomy.